Kebolehgunaan CD pembelajaran berbantu komputer bagi matapelajaran rekabentuk struktur 1 di Politeknik Sultan Haji Ahmad Shah, Kuantan, Pahang - Johari, Ishak (2003)
There has been a intense growth in the information technology field. The education field has also faced multiple changes and it is now a necessity to use different methods ofteaching in order to provoke the students to learn better and to have a better understanding in what they learn or about a certain subject. In order to fulfill this purpose, a Learning CD for students who are taking up a course in Diploma of Civil Engineering has been created. The actual purpose of this Learning CD is to encourage selflearning and to help students to have a better understanding in Design 1 which is a core subject for semester six Diploma students. This Learning CD was produced by using many fascinating multimedia criteria's such as a storyboard, audio, video, animation and text. The Learning CD is to encourage students to try an alternative way oflearning. The respondents for this research were 34 students who are currently in semester 6 and studying in Sultan Haji Ahmad Shah Polytechnic, Kuantan Pahang. This is a descriptive research where data collection and data analysis was done using the questionnaire. The questionnaire is divided into Part A and Part B which consist of 24 items. This research was done by distributing Learning CD's and questionnaires to each student in order to evaluate the usability of this product. On the whole this product got a positive feedback and the students were able to accept it as a learning alternative.